Resposta de mudas clonais de eucalipto cultivadas com hidrorretentor em diferentes níveis de disponibilidade hídrica - Gomes, Daniele Rodrigues (2013)
Water is a major factor limiting plant growth, being responsible for significant swings in crop productivity. Thus, polymers hidrorretentores and irrigation inclusion can assist in maintaining a constant production. This study aimed to evaluate the influence of the polymer under different irrigation management about growth, yield and quality of seedlings clonal of eucalyptus. The seedlings were rooted in the nursery company Fibria Cellulose S. A, Aracruz unit and transported to the city of Jerônimo Monteiro with 30 days. There was no intervention blade applied during the stay of seedlings in the nursery operational. The evaluated variables measured at the end of each phase of development of the seedlings were: adaptation, acclimatization, growth and hardening. It was used a completely randomized design (CRD) with four replications and the experimental unit consists of 20 plants. The experiment was arranged in a split-plot scheme, with irrigation at three levels, L1 = 100% ET0, L2 = 75% ET0 and L3 = 50% ET0; using hidrorretentor on two levels, D0 = 0.0 Kg m-3 , D1 = 0.50 kg m-3 and analyzed in four phases, Phase 0 = 35 days Phase 1 = 50 days, Phase 2 = 70 days and Phase 3 = 95 days after the cutting of the shoots, being evaluated at 35 days only variables: survival, height and stem diameter. The experimental data were subjected to ANOVA, and when significant developments were made of interactions and their average tests being compared by Tukey test at a significance level of 5%. To monitor the development and growth of the seedlings were evaluated for morphological variables: height, diameter, dry mass of shoots and roots; were determined to blade irrigated daily, the substrate water content and leaf water potential; and the classification of plants according to the quality standards set by the company Fibria S. A.. It was noticed a variation in seedlings in response to treatments which were submitted and evaluated phases. By analysis of variance showed a significant effect for triple interactions between variables: dry mass of shoots and roots, substrate water content and water potential in both schedules, while morphological variables, height and stem diameter occurred only double interactions between factors. For the study conditions, the blades 100% and 75% of ET0, determined by the equation of Hargreaves & Samani are suitable for irrigation of seedlings of hybrid clone of Eucalyptus grandis x Eucalyptus urophylla. The treatments which were returned 50% ET0, plant development when expressed in terms of height recorded significant decreases at the phases evaluated. The used time of 14 hours, for evaluation parameter leaf water potential does not manisfested different effects for plants, because it is a time of high metabolic activity with high rates of transpiration, should prefer in the morning hours. The standard of quality seedlings is not affected by the 25% reduction in blade applied, obtaining higher quality seedlings.